Pemanfaatan Limbah Plastik Menjadi Kerajinan Tangan Dalam Pengembangan Ekonomi Kreatif Pada Kelompok Bank Sampah Sultan Tanjung Kabupaten Lombok Timur - As'urin, B.; Sulastri, Sulastri; Junaidi, Junaidi (SOROT : Jurnal Pengabdian Kepada Masyarakat, 2025)
Non-organic waste is waste that cannot be decomposed. Non-organic waste comes from man-made materials such as plastic, glass, metal and other synthetic materials. If the waste is not processed further, it will damage the ecosystem and the environment. Therefore, the purpose of this service is to provide skills and training in developing plastic waste into various products that are appropriate and have a selling value as an effort in developing the creative economy. This service was carried out in the Sultan Tanjung Waste Bank group, East Lombok Regency with participants from the surrounding community. And the service team collaborated with LP2M as a resource person. The results obtained in this service are that this service program is able to increase community knowledge and skills related to the impact of plastic waste, its management and processing of plastic waste into art products. And this service program has succeeded in providing opportunities in developing the creative economy.